Positive magnetoresistance induced by fan-type phases in a spin-spiral magnet - Benito, L; Ward, R; Blamire, MG (2013)
We report on the positive magnetoresistance (MR) that accompanies the onset of fan-type magnetic structures in an epitaxially grown Dy/Y superlattice (SL). We find that MR ratios for current perpendicular to plane (CPP) and in-plane (CIP) geometries yield comparable values and a similar nonmonotonic dependence on the applied magnetic field H and temperature, which result in a maximum MR∼0.45% at T=110 K. We demonstrate that the rise in resistance is due to the increase in the number of superzone band gaps that accompanies the magnetization process of the anisotropic spin-spiral magnet, which reflects on the increasing complexity of the field-induced modulated magnetic structures. Furthermore, we find that the suppression of the giant MR in Dy/Y SL is due mainly to the combined action of chemical modulation and epitaxial strain effects. Finally, MR presents a linear (negative slope) and unsaturated scaling with H in the magnetized state, which is a clear fingerprint of magnon MR in highly anisotropic magnetic materials. © 2013 American Physical Society.